The ryanodine receptor is essential for larval development in Drosophila melanogaster - Sullivan, Kathleen M. C. (The National Academy of Sciences, 2000)
We have investigated the role of the ryanodine receptor in Drosophila development by using pharmacological and genetic approaches. We identified a P element insertion in the Drosophila ryanodine receptor gene, Ryanodine receptor 44F (Ryr), and used it to generate the hypomorphic allele Ryr(16). An examination of hypodermal, visceral, and circulatory muscle showed that, in each case, muscle contraction was impaired in Ryr(16) larvae. Treatment with the drug ryanodine, a highly specific modulator of ryanodine receptor channel activity, also inhibited muscle function, and, at high levels, completely blocked hypodermal muscle contraction. These results suggest that the ryanodine receptor is required for proper muscle function and may be essential for excitation-contraction coupling in larval body wall muscles. Nonmuscle roles of Ryr were also investigated. Ryanodine-sensitive Ca(2+) stores had previously been implicated in phototransduction; to address this, we generated Ryr(16) mutant clones in the adult eye and performed whole-cell, patch–clamp recordings on dissociated ommatidia. Our results do not support a role for Ryr in normal light responses.